Grab Malaysia Sdn. Bhd. / Haslinda Rahim, Nurul Ain Athirah Muhamad and Nurfarah Hidayu Abd Rahman - Rahim, Haslinda; Muhamad, Nurul Ain Athirah; Abd Rahman, Nurfarah Hidayu (2018)
Grab is a leading technological company that offers chauffeured rides transportation services varying from motorbikes, cars (5-seaters). Cars (7-seaters), and coach services in Southeast Asia, targeting both male and female varying from 18 to 50 years of age. It is discovered that Grab will have a competitive advantage over the competitors with efforts place into research and development of technologies that further enhance the current mobile application platform as well as many other factors that are elaborated in the report. Following which, the marketing department has come up with a new concept, introducing a new type of service with the incorporation of Grab's advance technology, and was tested repeatedly for months to tailor the service to suit the needs of the consumers. Grab provide car owner to legally transport public for a fee and it uses smartphone that provide to two of its main users which is driver and passenger to access into the application. The application is used by the driver to get information about who called him and same used to passenger to call driver. There are known problem about the application in relation to provide safety in both for driver and passenger. This report will further analyses about the stated problem above.